Optimizing Zakat, Infak, and Alms Management Through Broader Distribution Practices: Optimalisasi Pengelolaan Zakat, Infak, dan Sedekah Melalui Praktik Distribusi yang Lebih Luas - Ahmad Zidan Nasution; Yenni Samri Juliati Nasution; Sugianto Sugianto (Universitas Muhammadiyah Sidoarjo, 2025)
Community empowerment through faith-based financial management plays a crucial role in social welfare. Specifically, the Al-Ikhlas Jami Mosque in Bandar Setia manages Zakat, Infaq, and Sedekah (ZIS) funds to support local residents, though its usage remains largely consumptive. Despite the importance of ZIS, the current allocation—limited to four recipient categories (the poor, the needy, amil, and fi sabilillah)—reflects a narrow application of Islamic economic potential. Existing literature often neglects how local mosques can optimize ZIS for sustainable empowerment. This study aims to analyze the financial management practices of ZIS at the Al-Ikhlas Jami Mosque using a qualitative field research approach. Findings reveal a three-stage process: collection, distribution, and accountability, all executed in alignment with Islamic principles. However, the lack of diversification in beneficiary categories and weak monitoring mechanisms hinder its broader impact. The novelty lies in highlighting the mosque’s untapped potential to transform ZIS from consumptive relief into strategic empowerment tools. Implications include the need for policy reform to widen mustahik coverage and strengthen oversight, thereby enhancing the mosque’s role in socio-economic development. Highlights: Limited ZIS distribution focuses only on four mustahik groups. Management follows Islamic law but lacks strategic impact. Oversight and mustahik coverage need significant improvement. Keywords: ZIS Fund Management, Mosque Finance, Community Empowerment, Islamic Philanthropy, Financial Accountability